Interpreter of Eastern Traditions in Naat Recitation by Mohsin Ehsan - Rauf, Nuzhat; Izhar, Izharullah (sourcecoder, 2022)
"Naatia Poetry has a significant history in Urdu literature. This genre has always been considered but its current district recognition is the result of the publication of collections of Naatia poems. No strict structure and form is specified for writing Naatia poetry has a lot of variety yet in its diversity it highlights and enhances its distinct uniqueness". "Mohsin Ishan like other renowned Urdu poets has been part of the tradition of Naatia poetry writing. However, his style is Quite different from others which is his depiction of eastern culture and norms. Through the frequent depiction of eastern culture he intends to emphasize. The fact that the establishment of society, social norms tradition and culture start with the teaching of the Holy Prophet (PBUH) and eventually perfected with its practice". "Naatia poetry has a significant history in Urdu literature. Although from various references this genre has its own name but publications of various collections of Naatia poetry has given it that society. Social norms tradition and cultural norms all spring from the teachings of the Holy Prophet (PBUH) and are perfected through their practice".